POTENSI DESA WISATA PENGLIPURAN MENURUT MAHASISWA KEPARIWISATAAN POLITEKNIK PARIWISATA BALI - Anom Hery Suasapha (Pusat penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2020)
This article is written based on a research conducted on 2019. The research was a quantitative research, to determine the tourism potential of Penglipuran Village through the perception of Tourism Students of Bali Tourism Polytechnic. In doing so, quantitative as well as qualitative data were collected from primary and secondary source. The primary data which will be analyze were collected through survey method, using a self-administered questionnaire. The questionnaire was a Likert Scale Questionnaire, with five (5) respond category, consist of extremely disagree, disagree, neutral, agree and extremely agree. Secondary data were collected through documentation. Respondent were determined purposively, and on field, the surveyor determined the respondent accidentally. Data were then analyzed using Exploratory Factor Analysis, to produce result in the form of factors indicating the tourism potentials of Penglipuran Village. This research shows that the tourism potency of Penglipuran Village consists of those of Strength and those of Opportunity.